On Research of Possibility of Application of Acoustophysical Methods for Diagnosis of Malignant Formations in Living Organisms - Nalbandyan, V. V.; Mkhitaryan, S. A.; Badoyan, V. E.; Babayan, I. A.; Nalbandyan, A. H.; Mkrtchyan, A. H.
A methodology for diagnosing malignant tumors, in particular C–180–like sarcoma, in biological objects (white mice) is offered, utilizing a new contactless diagnostic method developed on the basis of modulation acoustic spectroscopy by scanning studied biological objects with modulated acoustic waves of different frequencies. Comparative analysis of the amplitude–frequency characteristics of response signals from the scanned healthy and diseased biological objects makes it possible to determine the presence and level of prevalence of malignant tumors.
Keywords: Physics